1994
DOI: 10.1093/rheumatology/33.12.1127
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fluid Muramic Acid in Acute Inflammatory Arthritis

Abstract: Presence of muramic acid, a bacterial cell wall component, was analysed by gas chromatography-mass spectrometry in synovial fluid (SF) of 40 patients with acute inflammatory arthritis. SF muramic acid was observed in 4/14 patients with acute, culture negative inflammatory arthritis of unclear origin. Each of these four patients had a history of a recent bacterial disease (pansinuitis, purulent leg ulcer, erysipelas, unexplained fever with suspicion of cholecystitis and urinary tract infection). In the bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Regarding the pathogenesis of human rheumatoid arthritis, it should be emphasized that (i) the E. aerofaciens strains used here originate in the normal gut flora of humans, (ii) degradation products derived from the normal gut flora are present in the circulation of healthy individuals (21,22), and (iii) bacterial CW debris has been demonstrated in the synovial tissues of patients with inflammatory arthritis (23,26,29,34,47). Therefore, the bacterial composition of the individual intestinal flora might represent a crucial factor contributing to the potential role of intestinal bacteria in the pathogenesis of rheumatoid arthritis.…”
Section: Vol 69 2001mentioning
confidence: 99%
“…Regarding the pathogenesis of human rheumatoid arthritis, it should be emphasized that (i) the E. aerofaciens strains used here originate in the normal gut flora of humans, (ii) degradation products derived from the normal gut flora are present in the circulation of healthy individuals (21,22), and (iii) bacterial CW debris has been demonstrated in the synovial tissues of patients with inflammatory arthritis (23,26,29,34,47). Therefore, the bacterial composition of the individual intestinal flora might represent a crucial factor contributing to the potential role of intestinal bacteria in the pathogenesis of rheumatoid arthritis.…”
Section: Vol 69 2001mentioning
confidence: 99%
“…(Adaptiert nach [1 [12][13][14][15][16][17][18]. Eine synoviale Lymphozytenproliferation als Immunantwort und spezifische DNA Analysen mittels PCR können hingegen wichtige Hinweise auf das Vorliegen einer infektiösen/ reaktiven Arthritis geben [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Fragestellungunclassified
“…It has also been reported that Mur is detectable in reactive arthritis. However, in the majority of cases, the levels are so low that detection proves elusive (27). These studies demonstrate the utility of nontraditional, gas chromatography-mass spectrometry (GC-MS) and more advanced GC-MS 2 techniques in demonstrating the presence of bacteria in human body fluids.…”
mentioning
confidence: 90%
“…Mur is readily demonstrated in body fluids in documented infection, including septic arthritis (7,14,27), bacterial meningitis (23), and urinary tract infections (2). It has also been reported that Mur is detectable in reactive arthritis.…”
mentioning
confidence: 98%